2022
DOI: 10.1021/acs.biomac.2c00917
|View full text |Cite
|
Sign up to set email alerts
|

Protein Desorption Kinetics Depends on the Timescale of Observation

Abstract: The presence of so-called reversible and irreversible protein adsorption on solid surfaces is well documented in the literature and represents the basis for the development of nanoparticles and implant materials to control interactions in physiological environments. Here, using a series of complementary single-molecule tracking approaches appropriate for different timescales, we show that protein desorption kinetics is much more complex than the traditional reversible–irreversible binary picture. Instead, we f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 58 publications
(97 reference statements)
3
14
0
Order By: Relevance
“…Wang et al reported the k d value of bovine serum albumin on the gold surface as 2.24 × 10 −3 s −1 . 51 This previous report supports that the slow desorption of ZnMb suppresses intraparticle diffusion in SP 30 and SP 50 in both processes.…”
Section: Thermodynamics Of Znmb Adsorption In the Silicasupporting
confidence: 68%
See 2 more Smart Citations
“…Wang et al reported the k d value of bovine serum albumin on the gold surface as 2.24 × 10 −3 s −1 . 51 This previous report supports that the slow desorption of ZnMb suppresses intraparticle diffusion in SP 30 and SP 50 in both processes.…”
Section: Thermodynamics Of Znmb Adsorption In the Silicasupporting
confidence: 68%
“…The corresponding simulated D p in Table is obtained when the k d is approximately 0.01–0.001 s –1 , indicating that the k d of ZnMb on the silica surface is of 10 –3 s –1 order. Wang et al reported the k d value of bovine serum albumin on the gold surface as 2.24 × 10 –3 s –1 . This previous report supports that the slow desorption of ZnMb suppresses intraparticle diffusion in SP 30 and SP 50 in both processes.…”
Section: Resultsmentioning
confidence: 68%
See 1 more Smart Citation
“…In reality, however, binding parameters are broadly distributed due to protein and NP surface heterogeneity, as was vividly shown by studies of individual adsorption events. [89] Structure-based computational modeling and simulation can also provide valuable insights into conformational changes of biomolecules interacting with surfaces. [97][98][99][100][101] At this stage, however, there are still severe challenges that need to be overcome to achieve realistic simulations of the adsorption process over longer times.…”
Section: Mathematical Modeling and Computer Simulationsmentioning
confidence: 99%
“…This makes SMT very suitable for acquiring the precise value of D in different timescales . The SMT enabled the scientists to understand details about, for example, the polymerization, the molecular movement in cells, and dynamics in complex environments, at the plasma membranes, and on solid–liquid and liquid–liquid , interfaces. Because SMT is essentially an imaging method, this technique can circumvent the inconsistent signal fitting and interpretation ,, and rule out concerns in which photophysical artifacts , and bulk fluid convection were erroneously interpreted as the variation of D .…”
Section: Introductionmentioning
confidence: 99%